Water : A Very Short Introduction - Finney, J. L. (John L.) (Great Clarendon Oxford University Press, 2015)
Water dominates the surface of Earth and is vital to life on our planet. It is a remarkable liquid which shows anomalous behaviour. In this Very Short Introduction John Finney introduces the science of water, and explores how the structure of water molecules gives rise to its physical and chemical properties. Considering water in all three of its states as ice and steam as well as liquid, Finney explains the great importance of an understanding of its structure and behaviour to a range of fields including chemistry, astrophysics, and earth and environmental sciences. Finney describes the role of water in biology, and ends with a discussion of the outstanding controversies concerning water, and some of the 'magical' properties which have been claimed for it.
Include Illustrations and Index
Keywords: Water. -- Hydrology. . -- Eau -- role of Water